2004
DOI: 10.1063/1.1763986
|View full text |Cite
|
Sign up to set email alerts
|

Lucky drift impact ionization in amorphous semiconductors

Abstract: The review of avalanche multiplication experiments clearly confirms the existence of the impact ionization effect in this class of semiconductors. The semilogarithmic plot of the impact ionization coefficient (α) versus the reciprocal field (1∕F) for holes in a-Se and electrons in a-Se and a-Si:H places the avalanche multiplication phenomena in amorphous semiconductors at much higher fields than those typically reported for crystalline semiconductors with comparable bandgaps. Furthermore, in contrast to well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 45 publications
7
63
0
Order By: Relevance
“…The experimental results on charge transport and effective quantum efficiency of charge photogeneration in a-Se blocking structures of HARP targets agree well with the theory of avalanche multiplication in a-Se [2,13] and previous studies [1,4,14] that showed avalanche multiplication in a-Se at electric fields in excess of 70 V/µm when drifting holes gain sufficient energy from the field to initiate impact ionization process. It should be noted that the presence of blocking layers for holes and electrons does not affect the hole transport mechanism.…”
Section: Resultssupporting
confidence: 87%
“…The experimental results on charge transport and effective quantum efficiency of charge photogeneration in a-Se blocking structures of HARP targets agree well with the theory of avalanche multiplication in a-Se [2,13] and previous studies [1,4,14] that showed avalanche multiplication in a-Se at electric fields in excess of 70 V/µm when drifting holes gain sufficient energy from the field to initiate impact ionization process. It should be noted that the presence of blocking layers for holes and electrons does not affect the hole transport mechanism.…”
Section: Resultssupporting
confidence: 87%
“…Recently, it has been possible to formulate an explanation for the avalanche multiplication mechanism in this class of semiconductors in terms of a suitably modified "lucky-drift" (LD) model. [47][48][49][50]. The LD model, as originally suggested by Ridley [51], allows carriers to undergo scattering while drifting in an electric field but, at the same time, the model allows the carriers to acquire energy, because momentum and energy relax at different rates.…”
Section: Dark Current and I-v Characteristics Of A-sementioning
confidence: 99%
“…There have been several studies that clearly show that such all solid-state devices with intrinsic avalanche gain represent the future of a-Se photodetectors in medical X-ray and functional γ-ray imaging applications [48,55]. For these applications, avalanche a-Se photosensors are intended to replace vacuum photomultipliers or silicon (Si) avalanche photodiodes (APDs) used to convert light emitted from a phosphor to collectable charges.…”
Section: Dark Current and I-v Characteristics Of A-sementioning
confidence: 99%
“…20 V/µm). This difference is attributed to intense elastic scattering due to disorder inherent to the amorphous structure [26,27].…”
Section: Resultsmentioning
confidence: 99%